RELATED FACTORS OF HEALTHY LATRINES BY COMMUNITY BAJO TRIBE IN BATUAWU VILLAGE, SUB DISTRICT SOUTH KABAENA, DISTRICT BOMBANA - Agus Darmawan; Taswin Taswin; Hastri Mailoa (Poltekkes Kemenkes Semarang, 2021)
In preventing environmental pollution due to unmanageable family toilets, there is a great need for public attention to the management of latrines that do not meet health requirements. This study aimed to determine the factors associated with the use of healthy latrines by the Bajo people in Batuawu Village Kabaena District South Bombana Regency. The type of study used was a cross sectional study. The population in this study were all Bajo people in Batuawu Village South Kabaena Subdistrict Bombana Regency, with a total of 48 families and a sample of 48 families. The analysis used was univariate analysis and bivariate analysis. The results showed that there was a relationship of knowledge with the use of healthy latrines has value ρ = 0.001 less than α = 0.05, there was a relationship with the use of healthy latrines had value ρ = 0.006 less than α = 0.05, there was a relationship between the availability of latrines and healthy latrines had value ρ = 0.005 less than α = 0.05, there was a relationship between the role of health workers and the use of healthy latrines had value ρ = 0.041 less than α = 0.05. Conclusions showed that there was a meaningful relationship between knowledge, attitude, availability of toilet facilities, the role of health workers with the use of healthy latrines by the Bajo people in Batuawu Village South Kabaena District Bombana Regency. Suggestions are in the form of the need to provide health education about the application of healthy latrines so that changes in people's lives occur that are in accordance with healthy behavior.